Dynamics of particle retention and physiology in Euonymus japonicus Thunb. var. aurea-marginatus Hort. with severe exhaust exposure under continuous drought. (15th September 2021) - Lin, Xintao; Shu, Da; Zhang, Jing; Chen, Jian; Zhou, Yuanhong; Chen, Chuwen
Abstract: Frequent drought events and particulate matter pollution from vehicular exhaust seriously affect urban plant growth and provisioning of ecological services. Yet, how plants respond physiologically and morphologically to these two combined stressors remains unknown. Here, we assessed particle retention dynamics and plant morphology and physiology of Euonymus japonicus Thunb. var. aurea-marginatus Hort. under continuous drought with severe exhaust exposure. Our results showed that continuous drought insignificantly lowered particle retention in each of three size fractions by 1.02 μg·cm −2 on average in the first 28 days, but significantly lowered total particle retention by 35.75 μg·cm −2 on the 35th day. We observed evident changes in morphology, leaf mass per area (LMA), pigments, gas exchange in all stressed plants. Compared with single stress, combined drought and pollution caused earlier yellowing and shedding of old leaves, significantly lowered LMA by 1.21 mg·cm −2, caused a greater decline in pigments and net photosynthetic rate ( P n ). Large particles may mainly explain pigment reduction, lower weekly LMA increases, and stomatal restriction, while coarse particles may be the main drivers of the decline in P n . Continuous drought mediated the influence of all three particle sizes on some parameters, such as weakening the impact of total particles on LMA, strengthening the impact of fine particles on photosynthesis. Our findings suggest that drought accelerates the physiological responses of plants to exhaust pollution. Under controlled severe exhaust pollution conditions, the optimal time to maintain high particle retention during continuous drought without decline in physiological conditions for E. japonicus var. aurea-marginatus was 14 days. Some additional interventions after 14 days (it could be postponed appropriately under field conditions) may help ensure healthy growth of plants and retention of particulate matter. Graphical abstract: Image 1 Highlights: Vehicle exhaust simulates serious particle pollution with continuous drought in OTC. Drought insignificantly lowers particle retention but makes old leaves wither earlier. Negative impacts of combined stressors on morphology, physiology are more evident. Optimal balance between particle retention and physiological state is on the 14th day.